Adolescents' Willingness to Commit to Safe Use and Disposal of Prescription Opioids. (1st April 2020) - Arora, Sanjay; Grewal, Sahib; Escamilla, Diandra; Menchine, Michael
Abstract: Introduction and aims: Leftover pills from prescriptions written in emergency departments are a key source of misused opioids among adolescents. Recently, the AMA has proposed emphasizing safe use and disposal of opioids, but patient perceptions on this proposed solution are largely unknown. In this study, we evaluate the willingness of adolescents to commit to pill security and safe opioid use in a clinical setting. Design and methods: In this prospective survey study conducted in an urban emergency department, a consecutive sample of adolescent patients between 15 and 22 years were asked about their exposure to opioids and attitudes toward the potential harm of opioid use/misuse and whether they were willing to consider to committing to pill security and safe opioid use in a clinical setting. We then assessed if willingness to commit varied based on attitude toward opioid misuse or previous experience with prescription opioids. Results: Eighty-one percent (91/113) of eligible patients agreed to participate. Overall 29.7% of adolescents had received a prescription for opioids and 40.7% had leftover pills. 87.9% were willing to commit to take opioids only as prescribed and 83.5% were willing to commit to disposing leftover opioids. Willingness did not vary by previous exposure to prescription opioids or attitudes toward recreational opioid use. Discussion and conclusions: Adolescents are highly willing to commit to safe opioid use and disposal regardless of previous exposure to opioids or attitude toward opioid misuse.